A preliminary study of visual memory and rule detection in fencing. A comparative study - Vertopoulos, E.; Tsolakis, C.; Remoundou, M. (Biology of Exercise, 2010)
The purpose of this preliminary study was to investigate possible differences among a group of fencers and a group of swimmers, in the visual memory task and the spatial anticipation task. 15 national level fencers (aged between 16 to 23 years) and 15 swimmers of a competitive swimming club (aged between 15 to 22 years), were studied. The Brixton Spatial Anticipation Test (BSAT) was used as a measure of executive functioning. The second test was the Visual Patterns Test (VPT), which measured visual short-term memory. The Digit Span subtest of the Wechsler Adult Intelligence Scale - III (WAIS) was also included as an estimate of general intelligence. There was a significant difference between fencers & swimmers in the BSAT, (F = 5.261, p = 0.030), while the analysis of the VPT test scores showed no significant differences among groups (F = 0.325 p = 0.573). In conclusion, fencers showed no better performance on visual memory, while they were superior in rule detection, comparing to swimmers. The long training fencing program, may greatly affects the speed of constitute information process as attributes of the decision making speed in national level fencers.